The Effect of Product Innovation, Service Quality, and Store Atmosphere on Consumer Loyalty at Puri Kawan Lodtunduh Gianyar Regency - Ningsih, Luh Kartika; Damayanti, Gusti Kadek Ayu Anggun Krisna; Yuliandari, Ni Kadek; Prastiwi , Ni Luh Putu Eka Yudi (Jurnal Manajemen, 2024)
Product development is not easy, innovation has an important role in a competitive market. Good service provides an unforgettable shopping experience that makes consumers loyal. The ability of a company to provide and create a comfortable atmosphere will affect consumer loyalty to the company. The purpose of this study was to determine the effect of product innovation, service quality and store atmosphere on consumer loyalty at Puri Kawan Lodtunduh, Gianyar Regency. The sampling technique in this study used a random sampling method by determining the number of samples using the slovin formula. The analysis technique used in this study is multiple linear regression analysis, coefficient of determination, statistical analysis t test and F test. The results prove that product innovation, service quality and store atmosphere have a positive and significant effect on consumer loyalty.